Interconnectedness of Global and Digital Assets: Cryptocurrencies, Gold, and Exchange Rates During 2021–2024 - Tsulatsa Nur Safiira; Maria Safitri; Amalia Nur Chasanah; Bara Zaretta (Economics and Digital Business Review, 2026)
Purpose: This study examines whether fluctuations in global assets—cryptocurrencies, gold, and the rupiah exchange rate—provide signals for movements in the Indonesian Composite Stock Price Index (JCI) during 2021–2024. Research Design and Methodology: Using 48 monthly time-series observations obtained from official financial data sources, the study applies a quantitative approach with multiple linear regression analysis using EViews 12 to evaluate both partial and simultaneous effects of the variables on the JCI. Findings and Discussion: The results show that cryptocurrency has a significant negative relationship with the JCI, while gold exhibits a significant positive relationship. In contrast, the exchange rate does not have a significant effect on the JCI. Simultaneously, the three variables contribute to explaining JCI variations, although with different magnitudes of influence, indicating differing roles of digital and traditional safe-haven assets in capital market dynamics. Implications: These findings suggest that investors and policymakers should consider global asset dynamics when interpreting Indonesian capital market conditions. Future research is recommended to include additional macroeconomic indicators and higher-frequency data to capture short-term transmission mechanisms more comprehensively.